Motor Ability Level and its Relationship With Football Playing Skills in 16-17 Year Olds - Humaedi; Andi Sultan Brilin Susandi Eka Wahyudhi; Fadli Ihsan (Tadulako Journal Sport Sciences And Physical Education, 2025)
Contemporary soccer performance relies heavily on a combination of basic physical abilities and mastery of proper technique. The purpose of this quantitative correlational study was to examine the relationship between motor skills and soccer playing ability and their impact on shooting ability in 40 adolescent athletes aged 16-17 years with N = 40. The descriptive statistics showed that the average motor skill was 150.45, and the average soccer skill was 100.12. The hypothesis was accepted because the correlation test showed a significant positive relationship with the observed r value (r0) = 0.521 with a probability value of 0.001 smaller than the critical value α = 0.05 (sig. 0.001 < 0.05). However, the regression test results showed that motor skills did not significantly influence shooting ability (p = 0.157). This study fills the research gap regarding the limitations of general motor skills in predicting complex specific techniques in late adolescence. According to recent research, motor skills only function as a basis for movement at the age of 16-17 years. However, accurate shooting requires functional technical skills and deeper maturity in movement mechanics. The results suggest that to optimize the performance of young athletes towards a professional level, coaches must combine fundamental physical strengthening with specific technical drills.